2016
DOI: 10.4172/2329-6887.1000204
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacovigilance Awareness among the Community Pharmacists and Pharmacy Students in the Turkish Republic of Northern Cyprus

Abstract: All healthcare professionals, other healthcare workers, patient caregivers, patients and even their families are all important to the healthcare system and pharmacists in every country are an important part of this system, and have a major duty to maintain and monitor the safety and efficacy of drugs as an integral part of their professional practice. Since pharmacovigilance is an indispensable part of the clinical discipline for detecting, assessing, understanding and prevention of adverse effects or any othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Of note, Doctor of Pharmacy (PharmD) students were significantly more knowledgeable in PV and ADR reporting when compared with BPharm students. 46 , 47 Likewise, in the study by Saygi et al, 34 higher knowledge score in PV was reported among the fifth year BPharm students than those in the first year of the pharmacy study. The level of knowledge regarding PV among the pharmacy students was found to be significantly associated with their previous exposure to the relevant topics, such as PV, ADR reporting, and pharmacoepidemiology.…”
Section: Perspective Of Undergraduate Pharmacy Studentsmentioning
confidence: 76%
See 1 more Smart Citation
“…Of note, Doctor of Pharmacy (PharmD) students were significantly more knowledgeable in PV and ADR reporting when compared with BPharm students. 46 , 47 Likewise, in the study by Saygi et al, 34 higher knowledge score in PV was reported among the fifth year BPharm students than those in the first year of the pharmacy study. The level of knowledge regarding PV among the pharmacy students was found to be significantly associated with their previous exposure to the relevant topics, such as PV, ADR reporting, and pharmacoepidemiology.…”
Section: Perspective Of Undergraduate Pharmacy Studentsmentioning
confidence: 76%
“… 47 In general, most studies reported that the pharmacy students had insufficient knowledge in PV or ADR reporting. 34 , 44 , 45 , 47 , 48 Approximately only 24.4%–62.4% of the pharmacy students were able to define PV and ADR correctly 44 , 48 , 49 , 51 and less than half of them knew the exact mechanism of ADR reporting (e.g., where to obtain ADR reporting form, when to report, and whom to report). 45 , 47 , 48 In certain studies, up to 88% of the surveyed students did not know how causality assessment of an ADR is being conducted, 49 and 70%–80% of them did not know about the PV program in the nation, 48 , 51 reflecting their poor knowledge in this area.…”
Section: Perspective Of Undergraduate Pharmacy Studentsmentioning
confidence: 99%